Is food insecurity higher among pregnant women in rural areas of Indonesia? - Azrimaidaliza Azrimaidaliza; Resmiati Resmiati; Gina Fajria Islami; Ulya Uti Fasrini; Annisa Dwi Apriliani (Gülhane Tıp Dergisi)
Aims: This study aimed to provide valuable insights to inform targeted interventions to alleviate food insecurity and improve maternal and fetal health outcomes, particularly in Indonesia. Methods: This cross-sectional study was conducted in rural West Sumatra, Indonesia, and investigated food security among 103 randomly selected pregnant women from Pesisir Selatan District. Participants were selected based on residency and consent, while those with severe illness or communication limitations were excluded. Data were collected using the validated Household Food Insecurity Access Scale. Statistical analysis, including Chi-square tests and logistic regression, was used to explore associations. Results: The study included 103 pregnant women, with a mean age of 25.22±3.35 years, ranging from 19 to 40 years. Results indicated a high prevalence of food insecurity (62.1%) among participants. Initial bivariate analysis showed a significant association between food insecurity and low maternal nutrition knowledge [odds ratio (OR): 6.378; 95% confidence interval (CI): 2.638-15.418; p≤0.001]. In the multivariate analysis, adjusted for maternal occupation and socioeconomic status, the association remained significant with p-values of 0.014 and <0.001, respectively. Multiple logistic regression revealed significant associations between food insecurity and maternal unemployment (OR: 9.147; 95% CI: 1.559-53.665; p=0.014) and low socioeconomic status (OR: 29.603; 95% CI: 8.800-99.584; p<0.001). Conclusions: These findings highlight the strong impact of unemployment and low socioeconomic status on food insecurity among pregnant women in rural West Sumatra. While maternal nutrition knowledge initially showed a significant relationship, its influence diminished in the context of other factors.